INVESTIGATING THE EFFECT OF MEDICAL AND NURSING SERVICES ON PATIENTS WITH FRACTURES, DIABETES AND HYPERTENSION IN THE HOSPITAL (OPERATING ROOM& ICU) (Journal of Pharmaceutical Negative Results, 2022)
A bone fracture in any part of the body can be very painful and cause a lot of pain to the patient. Especially if a fracture occurs in the pelvis, considering that the pelvis is an important part of the human body, it causes many problems for people. One of the factors that cause fractures in the body of patients is diabetes and high blood pressure in these people. Diabetes and high blood pressure do not cause each other, but people with diabetes are usually prone to other diseases such as high blood pressure and high blood cholesterol. Each of these things alone can cause damage to blood vessels and the occurrence of heart disease,stroke, kidney disease and other problems. Having all these diseases at the same time multiplies the probability of these injuries and disorders. High blood pressure increases the risk of diabetes-related complications, such as serious damage to the eyes, kidneys, and feet. If you have diabetes, try to control blood pressure to prevent heart attack or stroke. High blood pressure is very common in diabetic patients, especially type 2 diabetes, as more than half of type 2 diabetic patients also have high blood pressure. Having diabetes and high blood pressure at the same time doubles the patient's problems. Such patients are more prone to cardiovascular diseases, kidney disorders and strokes than others. Keeping the blood pressure of a diabetic patient in the range of 80/120 mmHg reduces the risk of diseases and heart attacks by 50% and the risk of kidney, eye and nerve damage by 33%. As a rule, the blood pressure of patients with diabetes should be lower than other people.